Slovenia : From Yugoslavia to the European Union - Mrak, Mojmir; Rojec, Matija; Silva-Jáuregui, Carlos (Washington, DC: World Bank, 2013)
The main objective of the book is to analyze Slovenia's threefold transition in the context of a broader transition process in Central and Eastern Europe and to contribute toward filling the obvious gap in the literature on this subject. The book provides an overview of the most important developments faced by Slovenia during its transition-the achievements, the problems, and the challenges-and discusses the lessons that have been learned and the main challenges that Slovenia can expect to face. Interdisciplinary in character, the book focuses on socioeconomic and political aspects and integrates them into the existing pool of knowledge about the transition process.